KOMUNIKASI ANTAR PRIBADI DALAM KELOMPOK BINA USAHA DI DESA LUENG BARO KECAMATAN WAYLA BARAT KABUPATEN ACEH BARAT - Khori Suci Maifianti; Devi Agustia (Jurnal Bisnis Tani, 2020)
Interpersonal communication is very important because interpersonal communication can increase mutual understanding between subordinate employees and superiors, and improve coordination of various different activities or tasks. Therefore effective communication will greatly determine the success of an organization or group so that the group stay intact for a long time. the purpose of this study is to see how interpersonal communication occurs in Bina Usaha groups. The results of this study show that interpersonal communication is less effective, it can be seen from not all components of communication available in interpersonal communication within the gorup. only the attitude of openness and positive, while emphaty, support, and similarity are also important in communication is lacking.